Construct Validity and Reliability: Perception of Teacher Competency Scale - Rakhmania, Raisa; Riyanti, Benedicta Prihatin Dwi; Purwanti, Margaretha (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
Early childhood teacher competency ensures high-quality programs and fosters student development. This competency comprises four key aspects: pedagogical, personality, social, and professional skills. However, Indonesia still lacks a psychometrically validated, perception-based competency scale that fully aligns with both national policy standards and internationally recognised frameworks. To address this gap, this research aimed to develop a self-inventory model of teacher competency. A 60-item questionnaire was sent to 249 early childhood teachers. Construct validity was examined using Exploratory and Confirmatory Factor Analyses. Convergent validity was confirmed by significant factor loadings, Composite Reliability, and Average Variance Extracted values. Criterion-related validity was supported by positive correlations with established measures of creative adaptability, perceived social support, teacher efficacy, and work engagement scale. The final analysis identified seven teacher competency dimensions. This scale also correlates with the other four measuring instruments. Analysis of Cronbach's Alpha Coefficient, Composit Reliability Value, and Average Variance Extract assessed reliability. The scale was refined to 45 valid items. This was followed by Measurement Invariance with Multigroup Confirmatory Factor Analysis, to evaluate potential differences in perceptions among groups categorised by educational background and teaching experience in their comprehension of the item questionnaire. The results revealed no significant differences in perceptions across either group type regarding the measuring instrument. This new scale is expected to enhance future research, educator training, and the quality of early childhood education.